To hell and back : Europe, 1914-1949 - Kershaw, Ian (Kershaw, Ian The Penguin history of Europe, 2015)
Introduction: Europe's era of self-destruction -- On the brink -- The great disaster -- Turbulent peace -- Dancing on the volcano -- Gathering shadows -- Danger zone -- Towards the abyss -- Hell on earth -- Quiet transitions in the dark decades -- Out of the ashes